Hubungan Asupan Lemak dan Serat dengan Kadar Kolesterol pada Penderita Diabetes Mellitus Tipe 2 - Ni Komang Wiardani; Ni Made Dewantari; Kadek Ima Purnami; P.A.Gita Prasanti (Jurusan Gizi, Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2018)
The regulation of fat and fiber intake plays an important role in the blood cholesterol level of diabetes mellitus patients (DM). Excessive intake of fat, especially saturated fat with low fiber intake in patients with type 2 diabetes can increase cholesterol levels. This triggers cardiovascular complications. The study aimed to determine the relationship between fat and fiber intake with blood cholesterol levels of type 2 DM patients. The study was an observational study with cross sectional design. The subjects of the study were outpatients at Sanglah Hospital, Denpasar, who were diagnosed with type 2 diabetes as many as 97 people. Data included total fat intake, saturated fat and fiber with a 1x24 hour recall method and total cholesterol levels using enzymatic methods using multicheck parameters. The results showed that 52.6% of the subjects were female and 47.4% were male. The average total fat intake was 52.1 g / day, saturated fat 15.0 g / day, fiber 22.5 g / day and an average cholesterol level of 210.4 mg / dl. Subjects with fat intake exceeded the recommended requirements of 77.4% total fat and 55.7% saturated fat. As many as 55.7% of research subjects with less fiber intake than recommended. Subjects with highcholesterollevels ( 200 mg / dl) were 56.7%. There was a significant relationship between fat and fiber intaketocholesterol levels (p 0.05, ? = 0.05).Keywords: fat intake, fiber intake, cholesterol level, type 2 DM